2009
DOI: 10.1348/026151008x334719
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of parental communication in modifying the relation between food advertising and children's consumption behaviour

Abstract: The aim of this study was to examine the effectiveness of various types of parental communication in modifying children's responses to television food advertising. In a combined diary-survey study among 234 parents of 4- to 12-year-old children, I investigated how different styles of advertising mediation (active vs. restrictive) and consumer communication (concept-oriented vs. socio-oriented) moderated the relation between children's advertising exposure and their consumption of advertised energy-dense food p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(140 citation statements)
references
References 43 publications
(63 reference statements)
6
129
4
1
Order By: Relevance
“…Three studies used cross-sectional survey designs (Buijzen, 2009;Harris and Bargh, 2009;Yu, 2011), and nine studies used experimental or quasi-experimental designs (Bickham and Slaby, 2012;Dhar and Baylis, 2011;Dixon et al, 2007;Ferguson et al, 2012;Goldberg, 1990;Gorn and Goldberg, 1982;Hindin et al, 2004;Potvin Kent et al, 2011a, 2012.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies used cross-sectional survey designs (Buijzen, 2009;Harris and Bargh, 2009;Yu, 2011), and nine studies used experimental or quasi-experimental designs (Bickham and Slaby, 2012;Dhar and Baylis, 2011;Dixon et al, 2007;Ferguson et al, 2012;Goldberg, 1990;Gorn and Goldberg, 1982;Hindin et al, 2004;Potvin Kent et al, 2011a, 2012.…”
Section: Methodsmentioning
confidence: 99%
“…These actions were aimed at reducing the volume of and children's exposure to advertising of foods HFSS, but did not explicitly focus on wider impacts. Six studies reported on educational measures to curb the influence of advertising for foods HFSS (Bickham and Slaby, 2012;Buijzen, 2009;Ferguson et al, 2012;Harris and Bargh, 2009;Hindin et al, 2004;Yu, 2011). These included media literacy interventions with parents or children, and parental communication with children relating to food advertising, and were aimed at improving diet quality, attitudes and beliefs towards food advertising.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The assumption behind this proposition is often that children can react as competent consumers if they understand the mechanisms of the market and are aware of persuasive attempts by retailers and manufacturers. Especially with a view to protecting children from undesired effects of advertising, this strategy seems to be prominent while other more restrictive strategies seem to be less suitable for protecting children (Buijzen 2009). …”
mentioning
confidence: 99%